Group‐based cognitive radio network formation without common channels. Issue 4 (1st July 2015) - Li, Xiukui; Zekavat, Seyed A. (Reza)
Abstract : To form cognitive radio nodes into a wireless ad‐hoc network, generally, globally or locally common channels are assumed to be available or some channels are dynamically selected as locally common ones. However, a cognitive radio node is not licensed to any channel for communication. With dynamic channel availability, neither locally nor globally common channels could be assumed available. Therefore, in this study, a new approach for cognitive radio network formation is presented that is not constrained by the availability of common channels. The proposed approach is based on the 'group' concept. Activated cognitive radio nodes form multiple 'groups' according to some criteria. Each group consists of a head node, some gateway nodes and ordinary nodes. During sensing phase, nodes sense channels and negotiate the channel and time slot assignment; thus, during data transmitting phase, each node is able to communicate with its different neighbour nodes in assigned channels during given time slots. Hence, nodes can be connected together to form a network without common channels and the network connectivity is improved. This study presents the network forming process including neighbour node detection, node communication, group formation, time slot assignment, channel assignment and medium access control protocol. Finally, simulations are conducted to investigate the network connectivity.